2
$\begingroup$

My question is how to prove monotone convergence theorem for infinite series without more advanced technique like counting measure. I see this used a lot. But looking through books like Rudin, the theorem for series or elementary proof is not to be found.

The theorem is:

For a sequence $x_{mn} \geq 0$ if $\lim_{m \to \infty} x_{mn} = y_n$ (monotonically increasing for $m$) then

$$\lim_{m \to \infty} \sum_{n=1}^\infty x_{mn} = \sum_{n=1}^\infty \lim_{m \to \infty} x _{mn}$$

$\endgroup$
2
$\begingroup$

This is a fairly easy consequence of Fatou’s Lemma for series, stating if $x_{mn} $ is nonnegative, then

$$\sum_{n=1}^\infty \,\liminf_{m \to \infty} \,\,x_{mn} \leqslant \,\liminf_{m \to \infty}\,\sum_{n=1}^\infty \, x_{mn}.$$

Consequently, if $x_{mn} \uparrow y_n$ then $x_{mn} \leqslant y_n$ for all $n$ and

$$\limsup_{m \to \infty} \, \sum_{n=1}^\infty x_{mn} \leqslant \sum_{n=1}^\infty y_n = \sum_{n=1}^\infty \,\liminf_{m \to \infty} \,\,x_{mn} \leqslant \,\liminf_{m \to \infty}\,\sum_{n=1}^\infty \, x_{mn}.$$

Thus, $\lim_{m \to \infty} \sum_{n=1}^\infty x_{mn} = \sum_{n=1}^\infty y_n$.

To prove Fatou's lemma, note that for all $k \geqslant m$ we have $\inf_{j \geqslant m} x_{jn} \leqslant x_{kn}$ and for every positive integer $N$,

$$\sum_{n=1}^N \inf_{j \geqslant m} x_{jn} \leqslant \inf_{k \geqslant m} \sum_{n=1}^N x_{kn} \leqslant \inf_{k \geqslant m} \sum_{n=1}^\infty x_{kn} $$

Taking the limit of boths sides as $m \to \infty$ followed by the limit as $N \to \infty$ gives us the result.

$\endgroup$
  • $\begingroup$ How do you get first inequality in second and third lines? $\endgroup$ – SAS Jan 23 '18 at 0:53
  • 1
    $\begingroup$ Assume you mean $\limsup_{m \to \infty} \, \sum_{n=1}^\infty x_{mn} \leqslant \sum_{n=1}^\infty y_n$ by second line. Since $0 < x_{mn} \leqslant y_n$ for all n we have $\sum_{n=1}^\infty x_{mn} \leqslant \sum_{n=1}^\infty y_n$ and taking the $\limsup$ as $m \to \infty$, we get the inequality since the RHS does not depend on $m$. $\endgroup$ – RRL Jan 23 '18 at 1:03
  • 1
    $\begingroup$ For $\sum_{n=1}^N \inf_{j \geqslant m} x_{jn} \leqslant \inf_{k \geqslant m} \sum_{n=1}^N x_{kn} $ -- again summing both sides of $\inf_j x_{jn } \leqslant x_{kn}$ we get the inequality without $\inf$ on the RHS. But this is true for all $k \geqslant m$, so taking the $\inf$ on the RHS preserves the inequality. $\endgroup$ – RRL Jan 23 '18 at 1:07
3
$\begingroup$

Cribbing from the way Rudin writes these things, one can give a proof that's the same as what Daniel Schepler said, except there's no need to split it into two cases:

Suppose that $$\alpha<\sum y_n.$$There exists $N<\infty$ so that $$\alpha<\sum_{n=1}^N y_n\le\sum y_n.$$

Now we certainly have $\lim_{m\to\infty}\sum_{n=1}^nx_{mn}=\sum_1^Ny_n$, so there exists $M$ such that $$\alpha<\sum_{n=1}^Nx_{mn}\le\sum_1^Ny_n,\quad(m>M).$$Hence for every $m>M$ we have $$\alpha<\sum_{n=1}^\infty x_{mn}\le\sum y_n.$$

$\endgroup$
1
$\begingroup$

Here's the outline of one simple proof:

First, suppose $\sum_{n=1}^\infty y_n$ converges. Then, for each $\epsilon > 0$, we can choose $N$ such that $\sum_{n=N+1}^\infty y_n < \frac{\epsilon}{2}$. Now, for each $m$, $\sum_{n=N+1}^\infty (y_n - x_{mn}) \le \sum_{n=N+1}^\infty y_n < \frac{\epsilon}{2}$. Whereas for $n=1, \ldots, N$, we can choose $M$ such that $y_n - x_{mn} < \frac{\epsilon}{2 N}$ whenever $m \ge M$. Therefore, whenever $m \ge M$, we have $0 \le \sum_{n=1}^\infty (y_n - x_{mn}) < \epsilon$, which implies the desired result. (So, the idea is: by being uniformly bounded by a convergent series, the tail of $\sum_{n=1}^\infty x_{mn}$ past some uniform $N$ doesn't matter that much, and then the rest of the terms are just a finite sum for which each term approaches $y_n$.)

Similarly, in the case $\sum_{n=1}^\infty y_n = \infty$ diverges, for any $R$ we can choose $N$ such that $\sum_{n=1}^N y_n > R + 1$. Now, we can choose $M$ such that whenever $m \ge M$, for each $n=1, \ldots, N$, we have $y_n - x_{mn} < \frac{1}{N}$. This implies that $\sum_{n=1}^\infty x_{mn} \ge \sum_{n=1}^N y_n - \sum_{n=1}^N (y_n - x_{mn}) > (R+1)-1 = R$. Thus, $\sum_{n=1}^\infty x_{mn} \to \infty$ as $m \to \infty$. (So, the idea in this case is that $\sum_{n=1}^N y_n$ can be made as large as we want, and then $\sum_{n=1}^N x_{mn}$ can be made close to this large value.)

$\endgroup$
0
$\begingroup$

Here's a constructive $\epsilon$ proof.

Let $\epsilon > 0$ be arbitrary. Consider the the smallest value of $N$ such that the partial sum $$\sum_{n=1}^N \lim_{m \to \infty} x _{mn}$$ is within $\epsilon/2$ of the actual sum.

Denote $\lim_{m \to \infty} x _{mn}$ by $x _{\infty,n}$ from now on.

Now let $M$ be such that whenever $m \geq M$ and $n \leq N$: $x_{\infty,n} - x_{mn} < \frac\epsilon{2N}$.

It follows that we are done, because for any $m\geq M$, $$\sum_{n=1}^\infty x_{\infty,n} \geq \sum_{n=1}^\infty x_{mn} \geq \sum_{n=1}^\infty x_{\infty,n} - \epsilon,$$

which can be proved in the following way:

$$\begin{aligned} x_{\infty,n} &> x_{mn}\\ \therefore \sum_{n=1}^\infty x_{\infty,n} &\geq \sum_{n=1}^\infty x_{mn}\\ &\geq \sum_{n=1}^N (x_{mn} )\\ &\geq \sum_{n=1}^N (x_{\infty,n} - \frac\epsilon{2N})\\ &\geq \sum_{n=1}^N (x_{\infty,n}) - \frac\epsilon{2}\\ &\geq \sum_{n=1}^\infty (x_{\infty,n}) - \frac\epsilon{2} - \frac\epsilon{2}\\ &= \sum_{n=1}^\infty (x_{\infty,n}) - \epsilon. \end{aligned}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.